The Influence of Financial Knowledge And Income On Financial Management Behavior with Financial Confidence as a Mediating Variabel from an Islamic Business Ethics Perspective: (A Study of Generation Z Employees in Bandar Lampung) - Aldo Faturizki; Vicky F Sanjaya; Yulistia Devi (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the influence of financial knowledge and income on financial management behavior with financial confidence as a mediating variable on Generation Z employees in Bandar Lampung. Using a quantitative approach, data were collected from 70 respondents through questionnaires and analyzed using SmartPLS4. The results show that financial knowledge has a positive and significant effect on financial management behavior, as well as on income In addition, financial confidence also has a significant effect on financial management behavior, and partially mediates the relationship between financial knowledge and income on financial management behavior. This study provides important implications for Islamic business ethics.